Background to the trade talks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Negotiating a Fait Accompli: the WTO incompatibility of the Lomé Convention Trade Provisions and the ACP-EU Negotiations. R Grynberg. Working Paper No. 38. European Centre for Development Policy Management Onze Lieve Vrouweplein 21 6211 HE Maastri